2010
DOI: 10.1016/j.jhealeco.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The importance of relative standards in ADHD diagnoses: Evidence based on exact birth dates

Abstract: This paper presents evidence that diagnoses of Attention-Deficit/Hyperactivity Disorder (ADHD) are driven largely by subjective comparisons across children in the same grade in school. Roughly 8.4 percent of children born in the month prior to their state’s cutoff date for kindergarten eligibility – who typically become the youngest and most developmentally immature children within a grade – are diagnosed with ADHD, compared to 5.1 percent of children born in the month immediately afterward. A child’s birth da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
143
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(170 citation statements)
references
References 39 publications
22
143
1
4
Order By: Relevance
“…Several studies (Elder, 2010; Evans, Morrill, & Parente, 2010; Halldner et al, 2014; Morrow et al, 2012; Zoëga, Valdimarsdóttir, & Hernández-Díaz, 2012) showed that relative age is a significant determinant of ADHD diagnosis and treatment. Overall, the youngest children in class are twice as likely as their classmates to receive a diagnosis of ADHD and medication.…”
Section: Birth Month Mattersmentioning
confidence: 99%
“…Several studies (Elder, 2010; Evans, Morrill, & Parente, 2010; Halldner et al, 2014; Morrow et al, 2012; Zoëga, Valdimarsdóttir, & Hernández-Díaz, 2012) showed that relative age is a significant determinant of ADHD diagnosis and treatment. Overall, the youngest children in class are twice as likely as their classmates to receive a diagnosis of ADHD and medication.…”
Section: Birth Month Mattersmentioning
confidence: 99%
“…A major concern arising from overdiagnosis of attention deficit hyperactivity disorder (ADHD) [1][2][3][4] is the frequent use of differ in their mode of action [8][9][10][11]. Psychostimulants modulate the monoamine transporters function, thereby increase the monoaminergic signaling, in one of two mechanisms; inhibition of monoamine reuptake, like cocaine, methylphenidate and amphetamine, or substance-type releasers, as amphetamine [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…This concern was amplified when various large-scale international studies noted an association between birth date and ADHD or ADHD medication (Elder 2010;Evans, Morrill and Parente 2010;Halldner et al 2014;Morrow et al 2012;Zoega, Valdimarsdóttir, and Hernández-Diaz 2012). According to these studies, younger children in a year group are much more likely to be diagnosed with ADHD and be prescribed ADHD medication than are elder children in a year group.…”
Section: Introductionmentioning
confidence: 99%